2011
DOI: 10.1002/clen.201000297
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pistachio Shells as an Adsorbent for the Removal of Zinc(II) Ion

Abstract: In this study, the removal of zinc(II) ion from an aqueous solution by pistachio shells (PS) is investigated. The dynamic behavior of the adsorption is examined on the effects of pH, adsorbent dosage, and contact time. The adsorption rates are determined quantitatively and simulated by the Lagergren first order, pseudo-second order, Elovich, and intra-particle diffusion kinetic models. The adsorption kinetic models are also tested for validity. The thermodynamic parameters, which are also deduced from adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
(34 reference statements)
0
10
0
1
Order By: Relevance
“…6 show that in the initial stages of the sorption process the amounts of Zn(II) retained on rapeseed increased sharply with increasing contact time of the phases, reaching values that remained then almost constant. A similar trend was observed for the case of removing Zn(II) by the pistachio shells (Turan and Mesei, 2011). In this context, it can be considered that the retention of Zn(II) ions on rapeseed takes place in two distinct steps, a relatively fast phase followed by a slower one.…”
Section: Effect Of the Contact Time And Kinetics Of Zn(ii) Biosorptiomentioning
confidence: 55%
“…6 show that in the initial stages of the sorption process the amounts of Zn(II) retained on rapeseed increased sharply with increasing contact time of the phases, reaching values that remained then almost constant. A similar trend was observed for the case of removing Zn(II) by the pistachio shells (Turan and Mesei, 2011). In this context, it can be considered that the retention of Zn(II) ions on rapeseed takes place in two distinct steps, a relatively fast phase followed by a slower one.…”
Section: Effect Of the Contact Time And Kinetics Of Zn(ii) Biosorptiomentioning
confidence: 55%
“…The adsorption process is economical, effective, simple, and versatile, and has become the most preferred treatment for heavy metals removal [103]. Knowing that fact, the high price and limited reusability are the key problems deterring the extensive application of a commonly used adsorbent, activated carbon [104]. In that perspective, biosorption has surfaced as a promising method with a high efficiency even at minute amounts, low cost, no additional nutrient requirements, easy handling, as well as zero detrimental effects towards the environment [105,106] Therefore, seaweed with the abovementioned criteria and together with its natural ecosystem balancing role has stimulated research conducted abundantly on varying types of seaweed to access the adsorbent performances and efficiencies in removing heavy metals in different wastewaters.…”
Section: Seaweed Application In Wastewater Treatmentmentioning
confidence: 99%
“…Going through the literature, it was found that the pistachio shell and similar types of lignocellulosic material are used for the adsorption studies of these dyes. In the literature, pistachio shell is also reported to have a wide range of adsorptive applications, ranging from dyes to heavy metals; thus, pistachio shell was selected as the SPE material [ 41 , 42 , 43 , 44 ]. To prepare the solid-phase material, pistachio shells were collected and washed, followed by drying till removal of the moisture content.…”
Section: Methodsmentioning
confidence: 99%